A SHORT ANALYSIS OF THE OF THE SMARTPHONES RELIABILITY - Adrian Stere PARIS (Fiabilitate şi Durabilitate)
A short analysis of some new results in the area of the reliability for smart mobile phones, the most used electronic devices, is of personal interest for every modern person. The strong competition induced by the globalization imposed necessary developments of the quality and reliability, fixed by ISO 9001-2015. The necessary huge availability of the mobile devices renders necessary new hardware and software efforts for reliability, especially for the first two competitors, Android and iOS. The paper presents mainly a short overview of a few recent statistical results, especially for the failure rates, and a comparison with older values (2011). An important growth of the reliability and availability is easy to detect, associated with the big efforts of the producers in testing these devices and huge development of applications.